Performance evaluation of conflict serializability against 2PL in Homogenous Distributed Database - Kaur, Harpreet; Kumar, Mritunjay; kumar, Gulshan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
There are many techniques in the recent years that provide the synchronization among the transactions using shared data like 2 phase locking protocol and time stamping in distributed database system. These techniques are efficient and provide fast transactional operations and serializable execution of the transactions. But these existing techniques like 2PL abort the transaction when a conflict occurs in transaction actions that result in degradation in the performance. In this dissertation we analyse the purposed techniques that provide the serial execution of the concurrent transactions. To achieve the serializability among the transactions in the distributed database Conflict serializability model is used that will provide serial execution of the transactions with in conflict actions of the transactions. The objectives of the scheme are achieved that provide the better performance than the existing 2PL schemes and achieve the consistency among the concurrent transaction execution. Performance is evaluated of CS model against the 2PL model in distributed database to sustain the synchronization in the transactions. Results illustrate that the proposed new scheme increase the performance by decreasing the abort rate in distributed environment.